Legal Protection for unregistered citizen at Healthcare and Social Security Agency (BPJS) - Andi Nur Awaliah Ramadhani; Zulkifli Aspan; Muh. Hasrul (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
Despite the reality that the JKN program is necessary for all Indonesian residents, there are still individuals who have not enrolled as JKN members. The purpose of this research is to evaluate and explain the application of individual health services and the government's impediments to citizens receiving legal protection under the BPJS health health social security system. The research approach adopted is one of normative legal research. A descriptive legal approach was adopted in the assessment process. According to the findings of this study, the application of individual health services in the framework of legal protection for people who are not enrolled in the BPJS Health social security system is restricted to the supply of health facilities. The state does not offer legal protection in the form of duty for delivering health care, because individuals who are not enrolled as BPJS Health participants will be registered as general patients, requiring them to pay for treatments individually or through private insurance. While the idea of BPJS Health as given in the BPJS Law requires everyone to register for BPJS Health, BPJS Health still has several inadequacies, which causes some individuals to be hesitant and unwilling to register as BPJS Health participants. The government cannot claim that the lack of legal protection in health services is the responsibility of those who do not register as BPJS Health participants, because this is a result or implication of the numerous deficiencies in health services that continue to employ BPJS Health.